Optimization of Pentahelix Collaboration in Tourism Development Management: Effective Strategies to Overcome Poverty - Maskuri Sutomo; Wahyuningsih; Muslimin; Mangun, Nudiatulhuda; Rombe, Elimawaty; Fattah, Vitayanti (Universitas Medan Area, 2024)
This study aims to develop a pentahelix collaboration model in tourism development as an effort to reduce poverty levels in Tojo Una-Una Regency, an area with great tourism potential but high poverty rates. In this study, qualitative methods were used, including Focus Group Discussion (FGD) and in-depth inter-views, to collect comprehensive data. SWOT analysis is used to identify strategies that can exploit strengths and opportunities while addressing existing weaknesses and threats. In addition, a matrix analysis is carried out to illustrate the division of roles in each proposed strategy. The findings of this study resulted in eight main strategies, including increasing the attractiveness of ecotourism, fostering re-gional cooperation, and increasing public awareness of environmental protection. This strategy is expected to improve the quality of human resources supporting tourism and strengthen tourism infra-structure in the region. Based on the results of this study, a matrix of collaboration between the government, academics, businesspeople, communities, and media was created, which is expected to be the foundation for joint efforts in overcoming poverty and accelerating tourism development in Tojo Una-Una.